A drying-free composite slag removal agent
By using raw materials such as bauxite waste slag, the dry-free composite slag discharge agent prepared by using raw materials such as bauxite waste slag, the problems of depletion of existing slag discharge agent resources, environmental pollution and high production costs are solved, and an efficient and environmentally friendly steelmaking process is achieved, and the time and effort in the preparation process are reduced.
Patent Information
- Application Number
- CN202510039785.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-04
AI Technical Summary
During the steelmaking process, the existing slag discharge agents have problems such as fluorite resource depletion, environmental pollution, high production costs and limited slag performance. The preparation of traditional slag discharge agents requires drying and processing, which is time-consuming and labor-consuming.
Bauxite waste slag is used as the main component, combined with iron oxide powder, sodium oxide powder, silicon calcium deoxidant and pregelatinized starch, and the addition of sodium oxide powder to exothermic and eliminate moisture, avoid drying treatment, and prepare a dry-free composite slag discharge agent.
The preparation of slag discharge agent without drying is achieved, which reduces production costs, shortens the factory time, and improves the strength, hardness, pass rate and life of slag discharge agent.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steel smelting, and in particular to a composite deslagging agent which does not require drying during the preparation process. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Slag removal is an important part of converter steelmaking in the steelmaking industry. Slag removal agents are introduced to remove harmful impurities such as sulfur, phosphorus and nitrate in molten iron, increase the fluidity of molten iron, and increase the iron content in converter slag. At present, slag removal agents are generally prepared with fluorite powder as the main raw material and calcium oxide and dolomite as auxiliary raw materials. Although it can accelerate the melting of slag, the main component of fluorite is CaF2, which has a serious corrosive effect on the furnace lining and increases the replacement frequency of steelmaking lining. In addition, fluorine will produce toxic gases after heating, which seriously affects physical and mental health and pollutes the environment. At the same time, fluorite resources are becoming increasingly depleted, and prices are rising, which increases the production costs of steelmaking enterprises. In recent years, some steel mills have eliminated fluorite slag removal for converters and switched to slag removal materials such as iron bauxite and dust removal ash. However, these slag removal materials have their own disadvantages, such as limited slag removal performance, environmental pollution, large impurities in molten iron, many harmful elements, severe splashing, etc., which bring inevitable and difficult-to-solve problems to steelmaking, resulting in inefficient steelmaking.
[0004] Bauxite slag is the polluting slag discharged when the aluminum industry extracts alumina. Generally, for every ton of alumina produced, 1.0~2.0 tons of bauxite slag are produced. As the world's fourth largest alumina producer, China discharges millions of tons of slag every year. A large amount of slag cannot be fully and effectively utilized and can only be piled up in the yard, occupying a large amount of land. During storage, dust and harmful gases will be generated, and the groundwater will be infiltrated and polluted, seriously affecting people's physical and mental health. The accumulation of a large amount of bauxite slag has caused many direct and indirect impacts on human production and life. It has been difficult to make harmless use of the slag. Therefore, it is urgent to reduce the output and harm of slag and realize multi-channel and large-scale resource recycling.
[0005] Wang Duogang et al.'s research shows that the introduction of Al2O3 into the converter slag system can reduce the melting point and promote slagging. When the mass fraction of Al2O3 changes in the range of 0-15%, the liquid phase area of the slag system increases accordingly. Pan Jianshe et al. verified that the deslagging agent containing Al2O3 can achieve the dephosphorization effect of converter steelmaking and reduce the consumption of limestone in the deslagging agent. Summary of the invention
[0006] In view of the above situation, the inventor believes that bauxite waste still contains a large amount of Al2O3 and metal oxides such as iron oxide, sodium oxide, calcium oxide, and magnesium oxide, which is very suitable as a slag removal agent raw material for converter steelmaking. Providing a slag removal agent with bauxite waste as the main component helps solve the problem of solid waste storage and is an environmentally friendly product.
[0007] In order to ensure the stability and effect of the slag remover, it will not agglomerate or explode during storage, and extend the storage period of the slag remover. In this field, it is generally required that the water content of the slag remover product be reduced to less than 0.5%. For example, the slag removers involved in patents CN115305313B and CN114131008B need to be dried to remove moisture after pressing. However, the bauxite waste slag raw material contains about 20%-30% moisture, and the moisture ratio is uncertain. The slag remover needs to extrude the mixed material into shape. Under pressurized conditions, the mixed material with a moisture content higher than 5% will adhere, loosen, and wrap around the mold, and cannot be extruded. Therefore, in the conventional slag remover preparation process, it is necessary to control the moisture in the raw materials and finished products, involving one or two steps of drying and drying treatment. Since the production of the slag remover is in tons, it takes a lot of manpower and material resources just to dry the product, which delays the delivery date and increases the cost.
[0008] In order to further reduce costs and increase efficiency, the present invention designs to add sodium oxide to the reaction raw materials. Since sodium oxide is sensitive to moisture and is easily deliquescent, it will undergo a violent chemical reaction when it comes into contact with water and will release a large amount of heat energy. The present invention has verified that the introduction of sodium oxide can quickly discharge the moisture contained in the waste slag and the finished product, and there is no need to dry the bauxite waste slag raw materials and the slag removal agent finished product, which greatly reduces the production cost and shortens the delivery time.
[0009] Based on the above technical effects, the present invention provides the following technical solutions: In a first aspect, the present invention provides a drying-free composite slag remover, wherein the raw materials and weight proportions of the slag remover are as follows: 55-80 parts of bauxite waste slag, 18-25 parts of iron oxide powder, 13-18 parts of sodium oxide powder, 3-7 parts of silicon-calcium deoxidizer, and 2-5 parts of pregelatinized starch.
[0010] The iron oxide powder is recycled iron powder. In one embodiment provided by the present invention, the iron oxide powder is an iron oxide product recovered from red mud, wherein the total iron oxide content is ≥80%, and in addition to iron oxide, it also contains a certain amount of aluminum oxide, sodium oxide and calcium oxide, and is a mixture of multiple oxide metals.
[0011] Likewise, the sodium oxide powder can also be a byproduct of red mud recovery.
[0012] The main components of the above-mentioned silicon-calcium deoxidizer are SiO2 and calcium carbonate CaO, wherein the silicon content is 50-65% and the calcium content is about 30-40%. In the converter steelmaking process, the silicon-calcium deoxidizer mainly plays the effect of deoxidation and warming, wherein silicon and calcium have a great affinity for oxygen, effectively removing the oxygen dissolved in the molten iron, and calcium has a great affinity for sulfur, and the desulfurization product is easy to float and remove in the molten iron, thereby removing impurities, improving the alloy yield, improving the performance of steel, and improving toughness and impact resistance. It has been verified that after the introduction of silicon-calcium deoxidizer, the strength, hardness, qualified rate and life of the slag removal agent can be increased by about 50%.
[0013] The above-mentioned pregelatinized starch can be used as a melt viscosity regulator in ironmaking or steelmaking, which will affect the slagging speed of the slag removal agent. In the steelmaking process, impurities in the melt that are difficult to remove are one of the main factors restricting the quality of steel. Pregelatinized starch can capture and absorb impurities in the melt to prevent them from mixing into the molten iron again, thereby improving the purity and quality of steel.
[0014] Furthermore, in a scheme with better effect, the proportion of the above raw materials is as follows: 55-80 parts of bauxite waste, 18-22 parts of iron oxide powder, 13-17 parts of sodium oxide powder, 3-7 parts of silicon-calcium deoxidizer, and 2-4 parts of pregelatinized starch; further, 57 parts of bauxite waste, 20 parts of iron oxide powder, 15 parts of sodium oxide powder, 5 parts of silicon-calcium deoxidizer, and 3 parts of pregelatinized starch.
[0015] The second aspect of the present invention provides a method for preparing the drying-free composite slag removal agent described in the first aspect, comprising the following steps: pre-mixing bauxite waste slag, iron oxide powder, and silicon-calcium deoxidizer, adding sodium oxide powder and accelerating stirring to assist heat dissipation, and after the temperature of the material system drops to below 85°C, adding pregelatinized starch and continuing to stir to obtain a mixture, and extruding the mixture to form the mixture.
[0016] Preferably, the premixing process can be carried out in a mixer at a stirring speed of 60-120 r / min and a stirring time of 10-20 min. After the sodium oxide powder is added, the stirring rate is increased to 100-150 r / min.
[0017] Preferably, the extrusion pressure value is 10~15kN.
[0018] The extruded product is a sphere or ellipsoid, which is sieved to make its size distribution uniform. After extrusion, it is cooled, packaged, and stored in a warehouse.
[0019] The present invention also provides an embodiment with better effect. In this embodiment, the bauxite waste is pretreated in the following manner: sodium oxide powder is added to water to prepare an alkaline solution, and the dosage ratio is 80~120g / L (calculated by the weight of sodium oxide powder). The bauxite waste and the alkaline solution are mixed and reacted in a closed reaction container for 4~6h, and the dosage ratio of the two is 80~120g:1L. After the reaction is completed, the solid part is sieved to retain.
[0020] In the above embodiment, the bauxite waste slag is pre-treated with alkali, which can effectively reduce the phosphorus and sulfur content in the waste slag raw material and the final molten iron, and the water removed by screening can be reused after adding alkali.
[0021] The third aspect of the present invention provides a method for using the drying-free composite slag removal agent described in the first aspect, comprising the following steps: adding molten iron and steel slag into a converter, the working oxygen pressure in the furnace is 0.5~0.9Mpa, the oxygen flow rate is maintained at 800~1200m³ / h, and the above-mentioned composite slag removal agent is added into the furnace after the furnace fire is stable, and the addition amount of the composite slag removal agent is 3~5% of the weight of the molten steel.
[0022] Compared with the prior art, the present invention has the following beneficial effects: 1. The deslagging agent provided by the present invention is a deslagging agent that does not require drying. After the above raw materials are mixed evenly, the moisture of the deslagging agent can be directly removed through the exothermic effect of sodium oxide. After shaping, the water content in the product drops to below 0.5%, and no further drying treatment is required.
[0023] 2. The raw materials of the slag removal agent in the present invention are mainly derived from waste materials of the aluminum industry. The main component, bauxite waste slag, is the polluting waste slag discharged when the aluminum industry extracts alumina. Iron oxide powder and sodium oxide powder are by-products of the aluminum smelting industry. Applying the above raw materials to the preparation of the slag removal agent is a recycling of waste, which reduces the production cost of the enterprise and alleviates the environmental pressure.
[0024] 3. In the traditional limestone-based deslagging agent, the CaO-FeO-SiO2 slag system is formed. CaO and SiO2 react to form and wrap the dicalcium silicate shell (C2S) on the surface of lime. The formation of the shell significantly improves the melting point of limestone, resulting in a slow solvent rate of the deslagging agent and poor fluidity. However, the deslagging agent in the present invention slags within 15 seconds after being added to molten iron, and soon forms a FeO-SiO2-Al2O3-Na2O slag system with low melting point and good fluidity. Before deep decarburization in steelmaking, the temperature of molten iron is relatively low, which is extremely beneficial to dephosphorization in thermodynamics. The deslagging agent in the present invention slags quickly, effectively improving the efficiency of the dephosphorization reaction in the early stage of steelmaking. DETAILED DESCRIPTION
[0025] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0026] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0027] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0028] The sources of the raw materials involved in the following examples are as follows: Bauxite waste residue: purchased from Weiqiao Group; Iron oxide powder: purchased from a mineral processing plant in Lingshou County, product model 190; Sodium oxide powder: purchased from a mineral processing plant in Lingshou County; Silicon calcium deoxidizer: purchased from a ferroalloy company in Henan, product model 6030; Pregelatinized starch: purchased from Jinan Biotechnology Co., Ltd.
[0029] Example 1 In this embodiment, a drying-free composite deslagging agent is provided, and the raw materials and weight ratios thereof are as follows: 57 parts of bauxite waste slag, 20 parts of iron oxide powder, 15 parts of sodium oxide powder, 5 parts of silicon calcium deoxidizer, and 3 parts of pregelatinized starch. The preparation method of the deslagging agent is as follows: (1) Weigh the above-mentioned raw materials in parts by weight, crush them, and pass them through a 200-mesh sieve. Add the bauxite waste slag, iron oxide powder, and silicon-calcium deoxidizer into a blender and stir at 60-120 r / min for 10-20 min to pre-mix them. Add sodium oxide powder and increase the stirring rate to 100-150 r / min to assist in heat dissipation. When the temperature in the stirring tank drops below 85°C, add pregelatinized starch and continue stirring for 20 min to obtain a mixture. At this time, the water content of the mixture is basically reduced to below 2.0%.
[0030] (2) Feed the above mixture into a ball press and set the pressure value to 10~15kN for extrusion. The product shape is a sphere or ellipsoid. The water content of the extruded product is less than 0.5%. After packaging, seal and store.
[0031] Example 2 In this embodiment, another drying-free composite slag removal agent is provided. The difference from Example 1 is that the raw materials and weight ratios of the preparation thereof are as follows: 55 parts of bauxite waste slag, 18 parts of iron oxide powder, 13 parts of sodium oxide powder, 3 parts of silicon calcium deoxidizer, and 2 parts of pregelatinized starch.
[0032] Example 3 In this embodiment, another drying-free composite slag removal agent is provided. The difference from Example 1 is that the raw materials and weight ratios of the preparation thereof are as follows: 80 parts of bauxite waste slag, 25 parts of iron oxide powder, 18 parts of sodium oxide powder, 7 parts of silicon-calcium deoxidizer, and 5 parts of pregelatinized starch.
[0033] Example 4 In this embodiment, another drying-free composite slag removal agent is provided, which is different from that in Embodiment 1 in that the bauxite waste slag is pretreated in the following manner: Add water to the sodium oxide powder to obtain an alkaline solution with a concentration of 80-120 g / L (calculated by the weight of the sodium oxide powder), place the bauxite waste in a closed reaction container, add the alkaline solution, and add a dosage ratio of 80-120 g:1 L. React for 4-6 hours under stirring conditions, cool to about 90° C., spread it to cool, filter through an 80 sieve to remove the liquid, and after no liquid drips, prepare the drying-free composite slag removal agent according to the description in Example 1.
[0034] Keep the solution that flows through the sieve and add an appropriate amount of sodium oxide powder (40-50 g of sodium oxide powder per liter of solution). It can be reused for the next pretreatment operation.
[0035] Comparative Example 1 In this embodiment, another drying-free composite deslagging agent is provided, which is different from Example 1 in that the sodium oxide powder is replaced with an equal dose of calcium oxide powder. Calcium oxide and sodium oxide also absorb water and release heat, and generate alkali, which is a commonly used desiccant product. During the research process of the present invention, calcium oxide was tried as a desiccant in the component, and the water content of the mixed material prepared by the same method as in Example 1 was still above 5%, which could not meet the water content requirement of the ball press machine.
[0036] Furthermore, the present invention doubles the dosage of the calcium oxide and prepares the mixture according to the method described in Example 1, so that the water content of the mixture is 4%, and the water content after extrusion is 1%.
[0037] Comparative Example 2 In this embodiment, another drying-free composite slag removal agent is provided, which is different from the embodiment 1 in that carboxymethyl cellulose is used as a binder instead of pregelatinized starch.
[0038] Performance Verification The performance of the above-mentioned slag removal agent was verified by the molten iron conditions of a steel plant in Shandong (Table 1). Steel and molten iron were added to the converter, and the lance was blown. The working oxygen pressure in the furnace was 0.7Mpa, and the oxygen flow rate was maintained at 1000m³ / h. After the furnace fire was stable, the composite slag removal agent in the above-mentioned embodiment and comparative example was added to the furnace, and the bottom blowing intensity was maintained at 0.03N / m³. Each embodiment group was tested for more than 100 heats, and the terminal molten iron content was measured. The results are shown in Tables 2 and 3: Table 1 Hot metal conditions and existing slag making process parameters (%) Table 2 Slag removal agent test results in Example 1 (%) It can be seen from the data in Table 2 that the composite slag removal agent in Example 1 and Example 4 can be slag removed in a very short time after being added to the molten iron, while the slag removal time of the slag removal agent in Comparative Example 1 is significantly prolonged. It is speculated that this may be because the presence of too much calcium reduces the flow effect of the system, resulting in slower slag removal and missing the early deep dephosphorization stage. Correspondingly, the molten iron at the end of Comparative Example 1 in Table 3 still contains a relatively high content of phosphorus. Similarly, after the binder was replaced in Comparative Example 2, the slag removal speed also slowed down.
[0039] In addition, it can be seen from Table 2 that after the composite slag removal agents of Examples 1 and 4 are introduced, the silicon content in the molten iron does not increase significantly, and the silicon content in the molten iron in Example 4 is more stable, which is beneficial to reducing the generation of converter slag, reducing the probability of splashing, and helping to extend the service life of the furnace lining.
[0040] Table 3 Comparison of test endpoints It can be seen from Table 3 that the slagging agents in Examples 1 and 4 have good dephosphorization and desulfurization effects, among which the effect of Example 4 is particularly outstanding, with a phosphorus removal rate of more than 90%, and the phosphorus content in the final molten iron is reduced to less than 0.002%.
[0041] According to the results in Table 3 above, the phosphorus and sulfur contents of the added heats were significantly reduced, and the iron content in the molten iron was increased.
[0042] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A drying-free composite deslagging agent, characterized in that: The raw materials and weight proportions of the slag removal agent are as follows: 55-80 parts of bauxite waste slag, 18-25 parts of iron oxide powder, 13-18 parts of sodium oxide powder, 3-7 parts of silicon-calcium deoxidizer, and 2-5 parts of pregelatinized starch.
2. The drying-free composite deslagging agent according to claim 1, characterized in that: The iron oxide powder is an iron oxide product recovered from red mud, and the total iron oxide content is ≥80%.
3. The drying-free composite deslagging agent according to claim 1, characterized in that: The sodium oxide powder is a recovered by-product of red mud.
4. The drying-free composite deslagging agent according to claim 1, characterized in that: The proportion of the raw materials for preparation is as follows: 55-80 parts of bauxite waste slag, 18-22 parts of iron oxide powder, 13-17 parts of sodium oxide powder, 3-7 parts of silicon calcium deoxidizer, and 2-4 parts of pregelatinized starch.
5. The drying-free composite deslagging agent according to claim 4, characterized in that: The proportion of the raw materials for preparation is as follows: 57 parts of bauxite waste slag, 20 parts of iron oxide powder, 15 parts of sodium oxide powder, 5 parts of silicon calcium deoxidizer, and 3 parts of pregelatinized starch.
6. The method for preparing the drying-free composite deslagging agent according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: pre-mixing bauxite waste slag, iron oxide powder and silicon calcium deoxidizer, adding sodium oxide powder to accelerate stirring to assist heat dissipation, and after the temperature of the material system drops below 85°C, adding pregelatinized starch and continuing stirring to obtain a mixture, and extruding the mixture to form the mixture.
7. The preparation method according to claim 6, characterized in that: The premixing process is carried out in a mixer at a stirring speed of 60-120 r / min and a stirring time of 10-20 min. After the sodium oxide powder is added, the stirring speed is increased to 100-150 r / min.
8. The preparation method according to claim 6, characterized in that: The bauxite waste is pretreated in the following manner: sodium oxide powder is added with water to prepare an alkaline solution at a dosage ratio of 80-120 g / L; the bauxite waste and the alkaline solution are mixed and reacted in a closed reaction container for 4-6 hours at a dosage ratio of 80-120 g:1 L; after the reaction is completed, the solid portion is sieved to retain.
9. The method for using the drying-free composite deslagging agent according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: adding molten iron and steel slag into a converter, wherein the working oxygen pressure in the converter is 0.5-0.9 MPa, the oxygen flow rate is maintained at 800-1200 m³ / h, and after the furnace fire is stabilized, the composite slag removal agent is added into the furnace, wherein the addition amount of the composite slag removal agent is 3-5% of the weight of the molten steel.
Citation Information
Patent Citations
A high-efficiency slagging agent for semi-steel tanks and its preparation method
CN114131008B